Depression and Psychological Stress Among Health Workers in Remote Areas in Indonesia - Idaiani, Sri; Waris, Lukman (Frontiers in Public Health, 2022)
Background: The Indonesian government launched the Nusantara Sehat program in 2015 under which teams of health workers are assigned to community health care centers in remote, border, and island areas for two years. The deployment to remote areas is likely to affect their psychological condition if they are not equipped with facilities and strong motivation. This study aimed to describe the psychological condition of health workers in remote areas in Indonesia, focusing on the proportion of the prevalence of depression and psychological stress. Materials and Methods: This cross-sectional study was conducted between April and December of 2018. Participants were 140 health workers placed in 26 community health care centers in 13 provinces. Interviews were conducted by enumerators using a questionnaire including questions from the Mini-International Neuropsychiatric Interview (MINI) and Self-Reporting Questionnaire-20 (SRQ-20). Results: Of the participants, 7.1% experienced depression, and 10.0% experienced psychological stress. Motivation was related to psychological stress in participants with an odds ratio of 0.218 (95% confidence interval = 0.065–0.729, p = 0.013). Health workers with high motivation tend not to experience psychological stress compared to individuals with lower motivation. Conclusion: Health workers with high motivation experience relatively low levels of psychological stress. To overcome stress, high motivation is needed to control psychological risk factors before and during placement.